Effect of Brain-Computer Interface Combined with Functional Electrical Stimulation on Upper Limb Function for stroke：A Meta-analysis - CHEN Songmei; GAO Jiiajia; ZHANG XiaoLin; LI Zhaoyuan; SHAN Chunlei (康复学报)
ObjectiveTo evaluate the effect of brain-computer interface (BCI) combined with functional electrical stimulation (FES) technology on upper limb motor function in stroke patients using Meta-analysis method.MethodsThe database of CNKI, WanFang Data, VIP, PubMed, EMbase, Web of Science, The Cochrane Library, ClinicalTrials.gov, and CT.gov were selected to collect the randomized controlled clinicals (RCTs) that studied on the effects of BCI and FES (BCI-FES) on upper limb motor function in stroke patients, from the journal established for March 2025. The primary outcome measures included Fugl-Meyer upper extremity motor function (FMA-UE), FMA-UE score difference, and modified Barthel Index (MBI). Meta-analysis was performed using RevMan 5.4 software after screening the literature, extracting information, and evaluating the risk of bias of the included studies were done independently by 2 researchers. Heterogeneity between the outcomes of the included RCTs was analyzed by χ2 test, and also combined with I2 quantitatively to determine the magnitude of heterogeneity after analysis. When the heterogeneity was small (I2≤50%, P≥0.1), the fixed-effects model was used for analysis; when the heterogeneity was large (I2>50%, P<0.1), the random-effects model was used for analysis.ResultsA total of 11 RCTs with 561 subjects were included. Meta-analysis showed that the FMA-UE scores were significantly higher in the experimental group than in the control group after treatment [MD=4.04, 95% CI (2.59, 5.48), Z=5.46, P<0.000 01]; and the FMA-UE scores differences were significantly higher than in the control group [MD=2.77, 95% CI (1.27, 4.28), Z=3.61, P=0.000 3]; and MBI scores were significantly higher than those of the control group [MD=7.41, 95% CI (2.47, 12.36), Z=2.94, P=0.003]. The results of subgroup analysis showed that for the subgroups of disease stage, first occurrence of stroke, and the subgroup of BCI-FES+other therapeutic measures, the post-treatment FMA-UE scores of the experimental group were higher than those of the control group (P<0.05). For the subgroups of disease stage, first occurrence of stroke, and BCI-FES+other therapeutic measures, the differences in post-treatment FMA-UE scores of the experimental group were higher than those of the control group. The differences were all statistically significant (P<0.05). For the BCI-FES+other therapeutic measures subgroup, the post-treatment MBI scores of the experimental group were all higher than those of the control group, and the differences were all statistically significant (P<0.05).ConclusionBCI-FES can effectively improve upper limb motor function and activities of daily living in stroke patients. In addition, the effect of BCI-FES treatment or combined with other rehabilitation measures is better in the first stroke and early recovery from stroke.